The ancestral symbiont sensor kinase CSK links photosynthesis with gene expression in chloroplasts. - Puthiyaveetil, S; Kavanagh, T; Cain, P; Sullivan, J; Newell, C; Gray, J; Robinson, C; van der Giezen, M; Rogers, M; Allen, J (2008)
We describe a novel, typically prokaryotic, sensor kinase in chloroplasts of green plants. The gene for this chloroplast sensor kinase (CSK) is found in cyanobacteria, prokaryotes from which chloroplasts evolved. The CSK gene has moved, during evolution, from the ancestral chloroplast to the nuclear genomes of eukaryotic algae and green plants. The CSK protein is now synthesised in the cytosol of photosynthetic eukaryotes and imported into their chloroplasts as a protein precursor. In the model higher plant Arabidopsis thaliana, CSK is autophosphorylated and required for control of transcription of chloroplast genes by the redox state of an electron carrier connecting photosystems I and II. CSK therefore provides a redox regulatory mechanism that couples photosynthesis to gene expression. This mechanism is inherited directly from the cyanobacterial ancestor of chloroplasts, is intrinsic to chloroplasts, and is targeted to chloroplast genes.